Broadband rectangular array slotted on resistive layer for multilayer microwave absorber - Suhaimi, Nur Anisafia (2017)
Microwave absorber is used to absorb unwanted signal in communication system. The higher the signal captured, the more the efficiency of the system. To improve the absorption performance, the slotted design based on the antenna will be develop and test to observe the absorption performance. The slotted will be arrange in the arrays to monitor the amount of the signal absorbed. The slotted will be develop in flat multilayer to observe the performance of the absorber in term of absorption. The biomass material also used in the design of the slotted since it will effect the performance of the absorber. The material use is mixed carbon that contain of carbon and paint. The CST microwave studio is used to design the slotted array and will be simulate to get the result to compare with the hardware of the design. The measurement of the hardware is using Arch method measurement and the result will be analyze together with simulation results. The result from the simulation and the measurement will be analyze and compare to conclude the absorption performance.